Hypertension clinical care in the era of coronavirus disease 2019: Practical insights from India - Tiwaskar, Mangesh; Koregol, Prabhakar; Krishnan, Hari; Agarwal, Dinesh; Hasan, Omer; Abhyankar, Mahesh; Revankar, Santosh; Kumar, Neeraj (Heart India, 2023)
Objective: The objective of this study was to seek the opinion of Indian health-care professionals (HCPs) about hypertension (HTN) care during coronavirus disease 2019 (COVID-19) era. Methods: HCPs' opinions (n = 2832) were recorded based on survey and round table meetings. Standard questionnaire consisting of nine questions pertaining to HTN care in COVID-19 was prepared, discussed, and evaluated by experts who treat patients with HTN during COVID-19 era. Results: Smoking/tobacco use, obesity, and comorbidities (diabetes/dyslipidemia) were ranked as the top three modifiable risk factors. A total of 37% and 33% of HCPs reported an increase in blood pressure (BP) during the lockdown period in 10%-20% and 20%-40% of hypertensive patients, respectively, who were on monotherapy. Around 35% of HCPs reported that 20%-30% of their patients with HTN showed uncontrolled BP (>150/100 mmHg). Dual-drug therapy in patients with uncontrolled BP was preferred by 56% of HCPs. Nearly 71% preferred dual combination for HTN management. In dual combination, 27% preferred angiotensin receptor blockers (ARBs) + diuretic, 26% preferred ARB + calcium channel blockers, and 18% preferred ARB + beta-blockers. The majority of HCPs (44%) consider that <30% of their patients with HTN check BP at home. A total of 47% of HCPs reported acute coronary syndrome as the most common HTN-related complication. The majority of HCPs (57%) considered that avoiding contamination during BP measurement is the challenging parameter. Around 32% considered self-BP monitoring (SBPM) as the best method to improve medication adherence. Conclusion: SBPM, combination therapies, and digital connect with patients are critical aspects of HTN management during COVID-19 pandemic.